1996
DOI: 10.1074/jbc.271.2.635
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Reverses the Misfolding Phenotype of the Most Common Cystic Fibrosis Mutation

Abstract: The common ⌬F508 mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) interferes with the biosynthetic folding of nascent CFTR polypeptides, leading to their retention and rapid degradation in an intracellular compartment proximal to the Golgi apparatus. Neither the pathway by which wild-type CFTR folds nor the mechanism by which the Phe 508 deletion interferes with this process is well understood. We have investigated the effect of glycerol, a polyhydric alcohol known to stabilize protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
316
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(332 citation statements)
references
References 22 publications
12
316
0
4
Order By: Relevance
“…We tested both these hypothesis by using chemical chaperones and by constructing double mutants. Chemical chaperones such as glycerol, dimethyl sulfoxide, trimethylamine N-oxide, and 4-phenylbutyric acid have been used to prevent mislocalization of CFTRΔF508 (33), mutants of the aquaporin-2 channel (23) and NaCl cotransporter mutants (34). In the present study, the expression and activity of the P351A and P351G mutants could be restored after treatment with 0.5 M glycerol.…”
Section: Discussionmentioning
confidence: 61%
“…We tested both these hypothesis by using chemical chaperones and by constructing double mutants. Chemical chaperones such as glycerol, dimethyl sulfoxide, trimethylamine N-oxide, and 4-phenylbutyric acid have been used to prevent mislocalization of CFTRΔF508 (33), mutants of the aquaporin-2 channel (23) and NaCl cotransporter mutants (34). In the present study, the expression and activity of the P351A and P351G mutants could be restored after treatment with 0.5 M glycerol.…”
Section: Discussionmentioning
confidence: 61%
“…However, maturation of ⌬Phe-508 is sensitive to the cell culture conditions; when cells were grown at reduced temperatures (Denning et al, 1992) or exposed to elevated levels of glycerol (Sato et al, 1996;Brown et al, 1996), an increase of mature ⌬Phe-508 CFTR at the cell surface has been observed. To explore the temperature/glycerol sensitivity of the processing mutants in CL3, cells expressing these mutants were shifted to 26°C for 48 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, such differences seem to occur regardless if these are naturally existing glycosylated and nonglycosylated forms of the same protein (our study) or experimentally generated ones. 32 Our observations may be also of relevance for strategies to induce cell surface expression of ER-retained misfolded but functional glycoproteins in which chemical chaperones, 21,33,34 calcium pump inhibitors 35 and low-molecular weight drugs and compounds 36 -38 have been applied to correct the traffic defect. In the case of the T126M AQP2, strategies to preferentially target the glycosylated form should be envisaged.…”
Section: Discussionmentioning
confidence: 99%